2019
DOI: 10.24018/ejers.2019.4.3.1155
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Physico-Chemical Properties of Spilled Crude Oil in Marine Sediments in Niger Delta

Abstract: This paper presents profile of the physico-chemical properties of study areas of the research. Most frequently, in the Niger Delta zone spilled oil in the marine sediments is prevalent. The research paper therefore focused at first instance to evolve the parametric control properties which have direct interactions with the spilled oil. Samples sediments A, B, C, and D were collected from the designated study areas of Southern Ijaw, Ekeremor, Ogbia, Brass and Nembe local government areas hosting the major oil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Oil pollution is detrimental to the environment and consequently the health of living beings, thus incurring tremendous costs in its cleanup. , Oil spills and industrial oily wastewater discharges have become the major sources of the common aquatic pollution. Studies have reported that, 30 years after an incident occurs, oil residual could still being detected, indicating that the potential indefinite persistency of oil in marine environments and sediments. , Due to the negative effects of oil spill and oily wastewater, treatments or mitigation strategies for oil–water separation have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil pollution is detrimental to the environment and consequently the health of living beings, thus incurring tremendous costs in its cleanup. , Oil spills and industrial oily wastewater discharges have become the major sources of the common aquatic pollution. Studies have reported that, 30 years after an incident occurs, oil residual could still being detected, indicating that the potential indefinite persistency of oil in marine environments and sediments. , Due to the negative effects of oil spill and oily wastewater, treatments or mitigation strategies for oil–water separation have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%
“…3−6 Studies have reported that, 30 years after an incident occurs, oil residual could still being detected, indicating that the potential indefinite persistency of oil in marine environments and sediments. 7,8 Due to the negative effects of oil spill and oily wastewater, treatments or mitigation strategies for oil−water separation have been investigated extensively.…”
Section: ■ Introductionmentioning
confidence: 99%